Differences in substance use by sexual orientation and gender among Jewish young adults in Israel - Hagit Bonny-Noach; Mally Shechory-Bitton (Israel Journal of Health Policy Research, 2020)
Abstract Background This study focuses on sexual orientation and gender-based differences among Israeli young adult substance use behaviors. In addition, it evaluates young adult perception of substance use and acceptance of substances use by close friends. Methods We conducted a cross-sectional study. A self-reported anonymous questionnaire was distributed to a convenience sample of 496 young-adults (age: M = 23.14, SD = 2.48), which included 126 heterosexual males, 128 heterosexual females, 131 gay men, and 111 lesbians. Results This study revealed significant sexual orientation and gender differences in all outcomes examined. Significant substance usage differences were found for same-sex orientation as 52% reported cannabis use and 24% reported using other illegal substances during the past 12 months compared to 34 and 6% (respectively) among heterosexuals. Significant gender differences were found, as male participants reported 50% cannabis use and 19% reported other illegal substance use in the past 12 months compared to 35 and 11% (respectively) among females. Additionally, compared with heterosexuals, gay men and lesbians perceived/assessed significantly higher substance usage rates among their close friends and higher levels of substance use acceptance by close friends. Regression models indicated the important role of respondent perceived and acceptance of substance use among close friends. Binge drinking, cannabis use, and other illegal substance use were positively associated with participants’ perceived substance use and substance use acceptance level by close friends, after controlling for gender, sexual orientation, age, and level of education. Conclusions Close friends and community norms can play an important role in shaping substance usage among young adults, especially among gay men and lesbians. The results of the current study highlight the need for developing prevention and harm reduction drug policies for Israeli young adults, especially for gay men and lesbians. Interventions should also focus on young adult peers and community norms related to substance use by professionals in educational, policy-making, and therapeutic contexts.